Late Carboniferous miospores from the Tarma Formation, Pongo de Mainique, Peru - Azcuy, Carlos Leopoldo (2002)
For the first time, a palynologic assemblage is described from the upper section of the Tarma Formation, Peru. It is dominated by monosaccate pollen grains with subordinate striate grains and very few spores. The abundance of Illinites unicus has allowed a revision of the systematic position of the form-genus Illinites. The assemblage is correlated with the Illinites unicus palynozone from the Amazonas Basin, and is considered to be of Westphalian C/Late Atokan age.